Indian agricultural policy at the crossroads - "Acharya,S.S.(ed.)" (New Delhi, 2001)
"The book is an outcome of a collaborative study addressing the highest priority issue which India faces today in agricultural sector policies. The main objective of the study was to document and analyse the impacts of past and current policies relating to trade, marketing, pricing, poverty reduction and employment generation, and also to identify policies/strategies in respect of trade, domestic markets, output and input pricing and other policy support. The authors take the position that the mix of policy changes propounded by them constitutes the best option for Indian policymakers today as far as agricultural sector is concerned.CONTRIBUTORS: S.S. Acharya, Ramesh Chand, D.P. Chaudhri, Dayanatha Jha, Praduman Kumar, Nelson Perera, Edgar J. Wilson, Zhang-Yue Zhou"
Keywords: Agriculture policy - India